Sinking deltas: trapped in a dual lock-in of technology and institutions. (1st September 2017) - Seijger, Chris; Ellen, Gerald Jan; Janssen, Stephanie; Verheijen, Esther; Erkens, Gilles
Abstract : In delta areas, flood protection structures and large-scale land reclamation are preferential water management strategies to cultivate soft delta soils. Over the past decades, river embankments, upstream dams, land reclamation, and groundwater use have intensified, and increasingly contribute to subsidence. In addition, the influence of institutions implementing these strategies has strengthened as they have acquired technical skills, knowledge, and vast financial resources. Sinking deltas are therefore trapped in a dual lock-in as dominating technology and institutions act as constraints to moving into a more long-term sustainable direction. Nine factors for the lock-in are introduced and illustrated for delta regions in Asia, Europe, and the US. To gain a better understanding of what researchers and practitioners can do to address the dual lock-in, a practical case is presented of Gouda, a Dutch subsiding city in search of more sustainable strategies and institutions. The paper ends with three steps to change the configuration of a dual lock-in: (1) getting to know the lock-in; (2) temporarily bypassing it; and (3) constituting a new, more sustainable lock-in. These steps should be further investigated in action-oriented research programmes with local experts, and targeted to policy processes and human behaviour in the sinking deltas.